Wound Infiltration for Enhanced Recovery After Cesarean Surgery in Rural Hospital: A Case Series - Roy Sando; Jimmy Wongkar (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2026)
Cesarean section is a major surgical procedure frequently associated with significant postoperative pain, which may delay mobilization and prolong hospital stay, particularly in rural hospitals with limited healthcare resources. Wound infiltration with local anesthetic represents a simple and practical analgesic component within the multimodal pain management strategy of the Enhanced Recovery After Cesarean Surgery (ERACS) pathway. This case series describes ten parturients scheduled for elective cesarean section with American Society of Anesthesiologists (ASA) physical status II and body mass index (BMI) < 30 kg/m2. All patients received regional anesthesia using subarachnoid block without intrathecal adjuvants. Local wound infiltration was performed before skin closure using 0.2% isobaric bupivacaine with adrenaline (1:200,000) along the incision margins. Postoperative outcomes included pain intensity was assessed by the Visual Analog Scale (VAS) at 2, 4, and 6 hours, as well as postoperative nausea and vomiting, early ambulation, early initiation of breastfeeding and length of hospital stay. Across all cases, low early postoperative pain scores were observed, with VAS score ≤ 2 during the first 4 hours and decreasing to 1 at 6 hours postoperatively. Eight patients achieved early ambulation and successfully initiated breastfeeding within 24 hours. Two patients experienced postoperative nausea and vomiting, which delayed mobilization and prolonged hospital stay beyond 24 hours. No wound complications or signs of local anesthetic systemic toxicity were observed. In this rural hospital setting, wound infiltration with bupivacaine and adrenaline was associated with favorable early postoperative outcomes and appears to be feasible, low-resource adjunct within ERACS protocols to support early recovery after cesarean delivery.